SITUATION-BASED LEARNING DALAM UPAYA MENINGKATKAN KEMAMPUAN CREATIVE PROBLEM SOLVING MATEMATIS SISWA PADA MATERI BILANGAN BULAT - Aqilah, Benazir; Isrok'atun, I.; Jayadinata, Asep Kurnia (Jurnal Pena Ilmiah, 2017)
This research is motivated by the low ability of mathematical elementary school student CPS on integer material. The purpose of this study is to determine whether the mathematical CPS ability of students who received SBL learning is better than students who received conventional learning. The instruments used in this research are Mathematical CPS capability test, master performance observation sheet and student activity, attitude scale questionnaire, and field notes. This research method is quasi experimental method with research design is pretest-posttest control group design. Sampling using cluster sampling technique and obtained sample that is SDN Cilimbangan as experiment class and SDN karangpawulang as control class. The results of the study with significance level Î± = 0,05 indicate that learning through SBL learning model is significantly better than conventional learning in improving students' mathematical CPS abilities.